2020
DOI: 10.3389/frai.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Variation and Change in 250 Years of English Scientific Writing: A Data-Driven Approach

Abstract: We trace the evolution of Scientific English through the Late Modern period to modern time on the basis of a comprehensive corpus composed of the Transactions and Proceedings of the Royal Society of London, the first and longest-running English scientific journal established in 1665. Specifically, we explore the linguistic imprints of specialization and diversification in the science domain which accumulate in the formation of "scientific language" and field-specific sublanguages/registers (chemistry, biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Similarly, Dubossarsky et al (2016) show that the grammatical categories words belong to play an important role in the way they shift through diachronic spaces. In our own work, we have observed that topological shifts in diachronic word embeddings are effects of the tension between lexical and grammatical changes (Bizzoni et al 2019;Bizzoni et al, 2020). Here, we build on these insights and specifically inspect tendencies towards grammaticalization.…”
Section: Computational Models Of Language Changementioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Dubossarsky et al (2016) show that the grammatical categories words belong to play an important role in the way they shift through diachronic spaces. In our own work, we have observed that topological shifts in diachronic word embeddings are effects of the tension between lexical and grammatical changes (Bizzoni et al 2019;Bizzoni et al, 2020). Here, we build on these insights and specifically inspect tendencies towards grammaticalization.…”
Section: Computational Models Of Language Changementioning
confidence: 90%
“…For example, in a study of the conditions of sound change Hume and Mailhot (2013) show that phonologization tends to affect elements linked to extreme degrees of surprisal and that both very low or very high surprisal exhibit low contributions to predicting outcomes in a system, i.e., to entropy reduction. In our own work, we have forwarded the hypothesis that scientific English has diachronically evolved towards an optimal code for communication among experts (Degaetano-Ortlieb and Teich, 2019;Bizzoni et al, 2020). Using information-theoretic measures (relative entropy, average surprisal), we have found that scientific English drifts away from general language over time, indicated by relative entropy (Kullback-Leibler Divergence) due to distinctive syntactic usage at clause level and a preference for complex nominal expressions.…”
Section: Diachronic Language Changementioning
confidence: 99%
“…Convergence is one effect leading to achieve this goal. Consider results from Degaetano-Ortlieb and Teich ( 2019 ) and Bizzoni et al ( 2020 ), who show a converging tendency in scientific writing for 17th–18th century English at both the lexical and the grammatical level. They argue that a decrease in variation, i.e., convergence on particular options, is beneficial for communication.…”
Section: Investigating Gender-specific Registerial Adaptation and Innovationmentioning
confidence: 99%
“…Considering the first point raised by Nevalainen and Traugott (2012, p. 3), while previous work on diachronic variation has mainly focused on one linguistic level [e.g., phonology; see also sociolinguistic (Labov, 1994(Labov, , 2001 and computational sociolinguistic studies (e.g., Eisenstein, 2015;Nguyen et al, 2016)], recent studies are increasingly considering several linguistic levels and possible interplay across linguistic levels in order to obtain a more comprehensive picture of change (Bermudez-Otero and Trousdale, 2012;Broccias, 2012;Degaetano-Ortlieb and Teich, 2019;Bizzoni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest curated corpora of this kind to date is the Royal Society Corpus (RSC; see Kermes et al (2016); Fischer et al (2020) for corpus creation and Menzel et al (2021) for metadata curation). The material of the Royal Society has been used in various diachronic studies to explore the development of English scientific writing and aspects such as the evolution of peer review and community-based editorial processes of scholarly journals (e.g., Halliday (1988); Degaetano-Ortlieb and Teich (2019); Fyfe et al (2020); Bizzoni et al (2020)).…”
Section: Related Workmentioning
confidence: 99%